Meningkatkan Kompetensi Pemrograman Siswa Melalui Pelatihan Pemrograman di MAN Kota Banjarbaru - Muhammad Bahit; Muhammad Alkaff; Eka Setya Wijaya; Fadliyanur; Erischa Marsela; Muhammad Ilham (CV. ALIM'SPUBLISHING, 2026)
The rapid advancement of digital technology has increased the demand for coding skills among students as one of the essential competencies in the Industrial Revolution 4.0 and Society 5.0 eras. However, many high school students have limited opportunities to learn programming through formal education. This community service activity aimed to improve the coding competence of students at MAN Kota Banjarbaru through intensive coding training that combined theoretical explanations with hands-on programming practice. The activity involved 12 students who participated in classroom instruction, guided practice, discussions, and evaluations using a structured questionnaire consisting of four dimensions: training quality, self-efficacy, coding competence, and learning interest. Evaluation results showed that participants perceived the training positively. The average scores for training quality (3.70), self-efficacy (3.44), coding competence (3.41), and learning interest (3.70) indicate that the program successfully enhanced students' understanding, confidence, and motivation to continue learning programming. The findings demonstrate that practical coding training is an effective community service approach for strengthening students' digital competencies and fostering greater interest in information technology).